Spatio-temporal analysis reveals active control of both task-relevant and task-irrelevant variables - Rácz, Kornelius; Valero-Cuevas, Francisco (Frontiers in Computational Neuroscience, 2013)
The Uncontrolled Manifold hypothesis and Minimal Intervention principle propose that the observed differential variability across task relevant (i.e., task goals) vs. irrelevant (i.e., in the null space of those goals) variables is evidence of a separation of task variables for efficient neural control, ranked by their respective variabilities (sometimes referred to as hierarchy of control). Support for this comes from spatial domain analyses (i.e., structure of) of kinematic, kinetic and EMG variability. While proponents admit the possibility of \textsl{preferential} as opposed to strictly \textsl{uncontrolled} variables, such distinctions have only begun to be quantified or considered in the temporal domain when inferring control action. Here we extend the study of task variability during tripod static grasp to the temporal domain by applying diffusion analysis. We show that both task-relevant and task-irrelevant parameters show corrective action at some time scales; and conversely, that task-relevant parameters do not show corrective action at other time scales. That is, the spatial fluctuations of fingertip forces show, as expected, greater ranges of variability in task-irrelevant variables (> 98% associated with changes in total grasp force; vs. only